Zakat Produktif sebagai Instrumen Pengentasan Kemiskinan untuk Masyarakat Usia Produktif - Risma Savhira Dwi Lestari; Mochammad Amaludhin Alwi (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2022)
The purpose of this study is to provide recommendations for the application of productive zakat as an instrument of poverty alleviation for people of productive age and to provide a choice of several productive zakat schemes. This study uses a qualitative method using literature studies to describe productive zakat schemes for alleviating poverty aimed at people of productive age. From these results it is hoped that the productive zakat scheme can really have an effect on alleviating poverty. The implication of this research is that it can build a mustahik mindset to try and work hard, so that mustahik can be empowered in their economy and become muzakki. ______________________ Tujuan dari penelitian ini adalah untuk memberi rekomendasi penerapan zakat produktif sebagai instrumen pengentasan kemiskinan untuk masyarakat usia produktif serta memberikan pilihan beberapa skema zakat produktif. Penelitian ini menggunakan metode kualitatif dengan menggunakan studi literatur untuk menguraikan skema zakat produktif untuk mengentas kemiskinan yang ditujukan kepada masyarakat usia produktif. Dari hasil tersebut diharapkan skema zakat produktif bisa benar-benar berpengaruh untuk mengentaskan kemiskinan. Implikasi dari penelitian ini adalah bisa membangun mindset mustahik untuk berusaha dan bekerja keras, sehingga mustahik bisa berdaya dalam perekonomiannya dan menjadi muzakki.